Arabic Learning Strategy In Early Childhood - Darmawati Darmawati; Ambo Dalle; Fikri Haekal Amdar; Abdul Aziz Bin Mustamin (Jurnal Ilmiah POTENSIA, 2021)
In today's digital era, everyone is required to master many things, both technology and foreign languages, especially Arabic. The introduction of Arabic from an early age is one way to master a foreign language well so that it can compete in the outside world. The purpose of this paper is to explain the importance of introducing Arabic to children from an early age and the benefits it can get. This study uses a qualitative research method, which is a research method that describes everything from the object under study. The results of the writing of this paper are in the form of an explanation of the importance of introducing Arabic to children from an early age and its benefits both from a child's psychological and academic perspective, as well as from a social perspective